2021
DOI: 10.1088/1742-6596/1918/5/052069
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of google classroom as a tool to support online science learning: a literature review

Abstract: The purpose of this article was to investigate the effectiveness of Google Classroom as a tool for support online science learning during pandemic COVID-19 in Indonesia. One of the impacts caused by COVID-19 in the education field is the implementation of online learning in all subjects, including science learning. This condition causes many teachers to use tools for online learning. Google Classroom is one of several tools to support online learning. Based on the literature review, this tool can manage class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…The Google Classroom app delivers services such as managing class schedules, providing online and offline communication, sharing files, creating and organising assignments, and providing feedback efficiently to facilitate users to interact and cooperate (Jamiludin et al, 2021;Widiyatmoko, 2021). Based on the social learning theory of constructivism (Vygotsky, 1987), the formation of fresh knowledge results during social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The Google Classroom app delivers services such as managing class schedules, providing online and offline communication, sharing files, creating and organising assignments, and providing feedback efficiently to facilitate users to interact and cooperate (Jamiludin et al, 2021;Widiyatmoko, 2021). Based on the social learning theory of constructivism (Vygotsky, 1987), the formation of fresh knowledge results during social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Past literature revealed numerous benefits in using GC as a learning tool, especially during the COVID-19 outbreak. The platform, for instance, allows educators to create and post various learning resources like pictures, videos, and links, manage students' assessments, give feedback to their students, and enable them to conduct live teaching and learning sessions [4]. In a study conducted by Hussaini et al [5], it was found that GC is dependable, effective, and efficient in enhancing learners' access and attentiveness in learning.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its benefit for students' language proficiency, it is also discovered that GC is an efficient learning device to support online science learning. Widiyatmoko [4], for example, found that GC can facilitate science teachers in managing classes, conducting laboratory activities, and making online tests.…”
Section: Introductionmentioning
confidence: 99%
“…Debido a la COVID-19, todos los países del mundo han decidido cerrar todas las instituciones educativas para prevenir los contagios (Ahmad et al, 2020;Dash et al;2021;UNESCO, 2021). En ese sentido, en el Perú, a partir del 11 de marzo del 2020, como medidas de prevención y control de la COVID-19 se dictó una serie de decretos supremos que declaran en estado de emergencia sanitaria a nivel nacional.…”
Section: Introductionunclassified
“…Además, Google Classroom es una plataforma de aprendizaje en línea gratuita con varias funciones que respalda el aprendizaje interactivo, divertido y significativo con una gestión del aula más flexible. Por ejemplo, Google Classroom puede ayudar a los profesores de ciencias a administrar clases, realizar actividades de laboratorio y realizar evaluaciones en línea(Widiyatmoko, 2021).Finalmente, Google Classroom se combina con Google Drive para la distribución de tareas, videos y uso compartido de archivos de presentaciones, y Google Calendar para programar el calendario de reuniones.En tercer lugar, Google Meet es una herramienta de videoconferencia con funcionalidades para crear e invitar a reuniones en línea, compartir pantalla, mensajería, diseños para visualización, grabar reuniones, traducciones automáticas de idiomas, entre otros. En ese sentido,Rusmansyah et al (2021) señala que, Google Meet facilita la interacción entre profesores y estudiantes como si estuvieran aprendiendo en clase directamente y paraSeptantiningtyas et al (2021) Google Meet influye de manera significativa la motivación de aprendizaje de los estudiantes, puesto que, los estudiantes consideran que es fácil de implementar y permite la flexibilidad en tiempo y espacio.Finalmente, existen otras herramientas de Google que destacan en el proceso de enseñanza y aprendizaje como por ejemplo Gmail, Grupos de Google, y Google Hangouts que disponen de funcionalidades para organizar mensajes correo, listas de distribución, organizar eventos y mensajería instantánea.…”
unclassified